JURIDICAL ANALYSIS OF PROVISIONING REMISSIONS TO CLASS II A PANCUR BATU CRIMINAL INCURRENTS - Venia Utami Keliat; Jumahirudin; Dara Nabilah Yusuf; Brainy Oloandri Pahala Bukit (Awang Long Law Review, 2022)
Giving remissions to prisoners is an order from the law as a stimulus so that prisoners are willing to undergo coaching to change behavior in accordance with the goals of the Correctional System. However, in its supervision involving institutions or agencies outside of the Correctional Institution, it is not accompanied by the existence of a firm regulation in its implementation.The method used in this journal is the sociological juridical method which means that the research method is about the suitability of the discussion of the problem with applicable legal provisions, and to see the reciprocity that arises between social life and law enforcement officers or agencies in this research. So in this study the sociological nature cannot be separated from the normative element, because government officials have carried out their duties based on statutory regulations in the form of laws, government regulations, presidential decrees, ministerial regulations and so on.From the results of observations and research at the Class II A Penitentiary, PANCUR BATU, the regulation in granting remissions by the Penitentiary is very advanced, the regulations are updated every time following the Indonesian Law. As well as in terms of the implementation and mechanism of granting remissions carried out by the Class II A Pancur Batu Penitentiary, there are still rights that are always given to inmates in granting additional remissions to prisoners. The Pancur Batu Class IIA Penitentiary always takes the initiative to socialize the steps for granting remissions to the latest regulations that have been socialized to prisoners.